Effects of bright light therapy on depressive symptoms and sleep quality among university students - Karólína Pétursdóttir 1995- (2019)
Depression and sleep disturbances are a big problem in today's society and studies have shown that these disorders are often concurrent. Over 300 million people around the world suffer from depression and 35-40% of adult individuals in the USA have problems with sleeping. One way to treat depression and sleep disturbances is the use of Bright Light Therapy (BLT). Many studies have examined the effectiveness of BLT with good results but the focus has been on participants with pre-existing health conditions. Hence, current study examined the effects of BLT on healthy individuals. Participants were psychology students at Reykjavík University aged between18-30 with 36 women and four men. A new form of BTL was used, the Ayo light glasses and participants were randomly assigned to use glasses with two different levels of brightness for 30 minutes each morning. They answered a questionnaire that included questions on depressive symptoms, sleep quality, insomnia and sleepiness before, during and after the intervention. Results showed a statistical difference between the two groups after the intervention in sleep quality but not in depressive symptoms. Keywords: Bright light therapy, depression, sleep quality Þunglyndi og skertur svefn eru stór vandamál í heiminum í dag og rannsóknir hafa sýnt að einkennin haldast oft í hendur. Meira en 300 milljónir manna um allan heim glíma við þunglyndi og rannsóknir hafa sýnt að 35-40% einstaklinga í Bandaríkjunum eiga við einhverskonar svefnvandamál að stríða. Ein af þeim leiðum sem hafa verið notaðar til að vinna gegn þessum vandamálum er ljósameðferð. Margar rannsóknir hafa kannað áhrif hennar en áherslan hefur verið á einstaklinga með fyrirliggjandi heilsuvandamál. Því var markmið núverandi rannsóknar að kanna áhrif ljósameðferðar á heilbrigða einstaklinga. Þátttakendur voru nemendur í sálfræði við Háskólann í Reykjavík og voru á aldrinum 18-30 ára. Þátttakendum var skipt upp í tvo hópa með mismunandi styrkleika ljóss. Ný tækni var notuð í ljósameðferðinni sem fólst í að ...